Podocyturia: A Clue for the Rational Use of Amiloride in Alport Renal Disease - H. Trimarchi; R. Canzonieri; A. Muryan; A. Schiel; A. Araoz; M. Paulero; J. Andrews; T. Rengel; M. Forrester; F. Lombi; V. Pomeranz; R. Iriarte; et al. (Case Reports in Nephrology)
No specific or efficient treatment exists for Alport syndrome, an X-linked hereditary disease caused by mutations in collagen type IV, a crucial component of the glomerular basement membrane. Kidney failure is usually a major complication of the disease, and patients require renal replacement therapy early in life. Microhematuria and subsequently proteinuria are hallmarks of kidney involvement, which are due to primary basement membrane alterations that mainly cause endothelial thrombosis and podocyte contraction and ulterior irreversible detachment. Commonly drug-based approaches include angiotensin-converting enzyme inhibitors and angiotensin receptor blockers, which are employed to reduce proteinuria and thus retard kidney disease progression and cardiovascular morbidity and mortality. However, as any hereditary disease, it is expressed as early as in the intrauterine life, and usually an index case is helpful to detect family-related cases. As no specific treatment exists, pathophysiologically based approaches are useful. The present case illustrates the reduction rate of urinary podocyte loss and proteinuria after amiloride administration and suggests the molecular pathways involved in Alport renal disease. Finally, podocyturia rather than proteinuria should be considered as an earlier biomarker of kidney involvement and disease progression in Alport disease.